Impact of COVID-19 Mitigation Policy in South Korea on the Reduction of Preterm or Low Birth Weight Birth Rate: A Single Center Experience - Sae-Yun Kim; So-Young Kim; Kicheol Kil; Young Lee (MDPI AG, 2021)
The government of South Korea implemented social distancing measures to control the coronavirus disease 2019 (COVID-19) outbreak. This study aimed to compare the composite preterm (PT) or low birth weight (LBW) birth rates during the COVID-19 pandemic period in South Korea to those during the prior decade, and to find out the associations of childbirth during the pandemic period with PT or LBW births. Over a ten-year period, this retrospective cohort study was performed in a single hospital in the Seoul metropolitan city. The COVID-19 period was defined as running from 22 March 2020, to 31 October 2020, and the pre-COVID-19 period as the sum of parallel periods from 2011 to 2019. Trends in composite birth rates were investigated, and logistic regression analysis was conducted to investigate independent factors associated with composite births. There were 246 and 2765 singleton deliveries during the COVID-19 period and the pre-COVID-19 period, respectively. The composite birth rate decreased from 16.5% to 9.8%. Childbirth during the pandemic was independently associated with a decreased composite birth rate (adjusted odds ratio, 0.563; 95% confidence interval, 0.355−0.844, p = 0.015). These findings suggested that the COVID-19 pandemic might provide an opportunity to find out preventive factors for PT or LBW births.